2019
DOI: 10.3390/app9153087
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Harsh Conditions on the Tensile Behaviour of Lap-Spliced Carbon Fiber Textile-Reinforced Mortar (TRM) with Different Surface Treatment Methods

Abstract: In the present study, the effect of harsh conditions on the tensile behavior of lap-spliced carbon fiber textile-reinforced mortar (TRM) with different surface treatment methods was investigated through the direct tensile test. The TRM coupons were exposed to three different harsh conditions: a chloride environment of 3.5 wt.% sodium chloride, a high temperature and humidity environment (50 °C and 95% relative humidity), and sustained load of 30% of the tensile strength during 60 days. In addition, two differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Distilled water, hydrochloric acid, and freeze-thaw cycles had a lesser impact on the performances. Tran et al (2019) evidenced that the lap-splice performances of carbon textiles can be affected by harsh conditions (saline, high temperature, humidity, sustained load). High temperatures affected the textile bonding, due to modifications in the organic resins used for impregnation (Liu et al 2019;Silva et al 2014; however, within certain temperature limits (≤200°C), TRM preheated and then tested at room temperature showed just small alterations (Colombo et al 2011;.…”
Section: Experimental Evidencesmentioning
confidence: 99%
“…Distilled water, hydrochloric acid, and freeze-thaw cycles had a lesser impact on the performances. Tran et al (2019) evidenced that the lap-splice performances of carbon textiles can be affected by harsh conditions (saline, high temperature, humidity, sustained load). High temperatures affected the textile bonding, due to modifications in the organic resins used for impregnation (Liu et al 2019;Silva et al 2014; however, within certain temperature limits (≤200°C), TRM preheated and then tested at room temperature showed just small alterations (Colombo et al 2011;.…”
Section: Experimental Evidencesmentioning
confidence: 99%
“…Table 1 summarises the mechanical properties of the grid, which is sand-coated (grain size of 0.3-0.8 mm) [29]. The sand-coated textile is employed in this study, as the surface coated textiles showed better bonding performance than uncoated textiles [15][16][17][23][24][25]. The mix composition of the mortar [16] is summarised in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…The minimum lap splice length of the textile grid is usually evaluated by a tensile test in accordance with a testing protocol, such as that specified in [ 22 ]. Numerous research groups [ 23 , 24 , 25 ] conducted direct tensile tests for TRC coupon specimens fabricated with lap-spliced textile grids. Overall, longer lap-spliced length of the textile grid gave better tensile performance than the shorter length.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the effect of humidity on behaviour of TRC is limited [ 1 , 140 , 141 ]. The tensile properties of alumina cement-based mortar reinforced with uncoated CFRP mesh (TRC-ALC) under a high temperature and humidity environment (50 °C and 95% relative humidity) were investigated.…”
Section: Durability Of Trcmentioning
confidence: 99%
“…The tensile properties of alumina cement-based mortar reinforced with uncoated CFRP mesh (TRC-ALC) under a high temperature and humidity environment (50 °C and 95% relative humidity) were investigated. TRC coupons were stored at a constant temperature of 50 °C and relative humidity of 95% in a chamber for 60 days, then the direct tensile test was performed one day later [ 141 ]. The stiffness of TRC-ALC under the temperature of 50 °C and relative humidity of 95% decreased obviously, compared with the specimens exposed at room temperature and humidity (COM).…”
Section: Durability Of Trcmentioning
confidence: 99%